Climate Change Anxiety Assessment: The Psychometric Properties of the Polish Version of the Climate Anxiety Scale - Larionow, Paweł; Sołtys, Michalina; Izdebski, Paweł; Mudło-Głagolska, Karolina; Golonka, Justyna; Demski, Maksym; Rosińska, Maja (Frontiers in Psychology, 2022)
The Climate Anxiety Scale (CAS) is a 13-item questionnaire for assessing climate anxiety (CA) as a psychological response to climate change. The CAS consists of two subscales, namely, cognitive impairment and functional impairment. This study aimed to validate the Polish version of the CAS. The sample included 603 respondents (344 females, 247 males, and 12 non-binary), aged 18–70 years (M = 25.32, SD = 9.59). Based on the exploratory factor analysis results, we proposed a 3-factor solution (i.e., intrusive symptoms, reflections on CA, and functional impairment), which seems to be theoretically more consistent with the content of the CAS statements. The confirmatory factor analysis showed that the original 2-factor solution and the 3-factor one had a satisfactory and a good fit to the data, respectively, as well as both were invariant across different gender, age, and educational level categories. Despite the fact that the 3-factor solution had the best-fit indices, we recommended to examine the CAS structure in different samples and use the overall CAS score in cross-cultural research. Cognitive and functional impairment subscales were positively correlated with personal experience of climate change, behavioral engagement, environmental identity, and environmental motives, but they were negatively correlated with climate change denial and sense of safety. The CAS subscales were correlated with depressive symptoms, but contrary to expectations, they were not associated with anxiety symptoms and any cognitive coping strategies. The Polish version of the CAS has satisfactory psychometric properties. Overall, we reported low CA levels in the Polish sample. Women and younger people experienced higher CA.